MEDB-40. RUNNING FOR INCLUSION IN SIOPE PNET5 MB. (3rd June 2022) - Massimino, Maura; Boschetti, Luna; Minasi, Simone; Erbetta, Alessandra; Chiapparini, Luisa; Mastronuzzi, Angela; Miele, Evelina; Barra, Salvina; Scarzello, Giovanni; Cavatorta, Claudia; Antonelli, Manila; Gandola, Lorenza; et al.
Abstract: Enrolling medulloblastoma(MB) patients in the PNET5 protocol is a daily problem in Italy; since June 2015, 59 cases have been enrolled in 13 centres. So far, 44 of the 103 patients claiming for eligibility did not enter the protocol: 13 metastases, 5 for residual, 20 having exclusion criteria, 4 insufficient frozen material, 2 failure to comply with the correct procedures. No case was lost due to delayed centralization, which is respected even with committing weekends; review of the radiation plan was performed on Saturday for 2 cases, and radiotherapy began on the same day. We made some procedural changes to meet expected deadlines; each local centre notifies the national coordinator of a possible case's existence at MRI diagnosis, of the expected surgery date as well as its realization. MRI imaging is reviewed within 2 days after centralization. Paediatricians notify the national coordinator and pathology/biology reference centre of the MB diagnosis; the shipment of frozen tissue, blood and FFPE is booked. A slot is reserved to priority perform the central pathology review, as well as central molecular diagnosis of genetically defined subgroup (WHO classification) upon receipt of the frozen material. Upon receipt of the FFPE and frozen material, the national reference centre undertakes a double-check with the national coordinator and the local treatment centre to validate the eligibility. Within the 7th day from the receipt of the material: IHC, MYC/MYCN, Monosomy 6, beta-catenin mutation and methylation array are performed. Priority execution of somatic (blood control) sequencing of the PTCH, SUFU, and TP53 genes is also triggered for SHH-activated MB, with the deadline on the 15th day. So far we have had 99% agreement between molecular subgrouping and methylation array. CONCLUSIONS: PNET5 requirements are multiple and changing over time; difficulties may and must be overcome by mutual fast collaboration.